1981
DOI: 10.1136/bmj.283.6301.1215
|View full text |Cite
|
Sign up to set email alerts
|

Another smoking hazard: raised serum IgE concentration and increased risk of occupational allergy.

Abstract: Individual smoking histories of a general population sample and of two groups of workers exposed to occupational allergens were related to serum IgE concentrations and results of radioallergosorbent and prick tests in the workers.The geometric mean IgE concentration was higher in smokers than in non-smokers. The distribution of serum IgE values in the two groups showed an apparent difference, with a bimodal appearance in the smokers.Evidence of sensitisation against occupational allergens was more common in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
98
5
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(122 citation statements)
references
References 12 publications
18
98
5
1
Order By: Relevance
“…Atopic markers such as increased specific IgE levels and immediate skin reactivity to common inhalants seem to be even less common in smokers [20]. Smoking has however been found to be a determinant of IgE-mediated sensitization to such occupational agents as psyllium [21] and platinum salts [22]. However, smoking was not found to be associated with the development of specific skin reaction to laboratory animals in previously published studies by CULLINAN et al [2] and HEEDERIK et al [7].…”
Section: Discussioncontrasting
confidence: 37%
“…Atopic markers such as increased specific IgE levels and immediate skin reactivity to common inhalants seem to be even less common in smokers [20]. Smoking has however been found to be a determinant of IgE-mediated sensitization to such occupational agents as psyllium [21] and platinum salts [22]. However, smoking was not found to be associated with the development of specific skin reaction to laboratory animals in previously published studies by CULLINAN et al [2] and HEEDERIK et al [7].…”
Section: Discussioncontrasting
confidence: 37%
“…Cigarette smoking also appears to increase risk of IgE-mediated occupational asthma. Workers who smoke and have been exposed to platinum salts, acid anhydrides, snow crab, green coffee beans, and ispaghula have been shown to have greater risk of developing occupational asthma than their nonsmoking coworkers (14). In contrast, for most sensitizing agents that cause asthma through mechanisms not involving specific IgE antibodies, such as diisocyanates and western red cedar, atopy and smoking do not appear to be risk factors (15,16).…”
Section: Definition/classification Of Occupational Asthmamentioning
confidence: 92%
“…Some studies have found higher serum total IgE levels in men than in women (2, 3), but other studies did not find these differences (7)(8)(9). Several studies reported higher serum total IgE levels in smokers (6,10,11). However, it is unknown whether any sex differences in serum total IgE levels may be explained by sex differences in smoking habits.…”
mentioning
confidence: 96%